Revisión de los Impactos Sobre los Proyectos de Minería en el Departamento del Cauca y la Repercusión en Comunidades Ancestrales del Pueblo Indígena Nasa (2022)
This monograph is carried out with the objective of identifying the environmental impacts generated by mining projects in the department of Cauca and the repercussion they have on the Nasa indigenous community. For this, a qualitative, descriptive and documentary methodology is presented. The results showed that there are damages generated by mining activities to the indigenous community, due to the intervention, alteration of the natural environment and discharge of metals during the extractive process; In the same way, the separation of the material from the subsoil is another harmful consequence that endangers the health of the inhabitants. On the other hand, the Nasa community, as well as other indigenous peoples, do not have the application of political guarantees in practice that protect the non-intervention of their territory and therefore respect for their customs, since the technical guarantee is put above social welfare, which neglects their ancestral knowledge and at the same time puts the indigenous community at risk. It was identified that, among the actions that mitigate environmental impacts arising from mining projects in the Nasa indigenous community, is: taking into account the inclusion of ancestral knowledge and the due process of intervention in their territories. It is concluded that the actions that reduce the environmental effects generated by mining projects in the Nasa indigenous community are based on the protection, preservation and improvement of ecosystems that are essential, but these policies have not been effective: it is important to consider that The territory must allow the guarantee of minimum living conditions for its inhabitants and, therefore, there is an urgent need to promote meetings around these areas of governance to implement practices other than the criminalization of mining and its police control.